Induction of programmed cell death in human hematopoietic cell lines by fibronectin via its interaction with very late antigen 5. - Hiroyuki Sugahara; Yuzuru Kanakura; T Furitsu; Katsuhiko Ishihara; Kenji Oritani; Hirokazu Ikeda; H Kitayama; Jun Ishikawa; Koji Hashimoto; Yoshio Kanayama (1994)
Extracellular matrix (ECM) molecules such as fibronectin (FN), collagens, and laminin have important roles in hematopoiesis. However, little is known about the precise mechanisms by which ECM molecules regulate proliferation of human hematopoietic progenitor cells. In this study, we have investigated the effects of ECM molecules, particularly of FN, on the proliferation of a myeloid leukemia cell line, M07E, which proliferates in response to either human granulocyte/macrophage colony-stimulating factor (GM-CSF) or stem cell factor (SCF). The [3H]thymidine incorporation and cell enumeration assays showed that FN strikingly inhibited GM-CSF- or SCF-induced proliferation of M07E cells in a dose-dependent manner, whereas little or no inhibition was induced by collagen types I and IV. The growth suppression of M07E cells was not due to the inhibitory effect of FN on ligand binding or very early events in the signal transduction pathways from the GM-CSF or SCF receptors. DNA content analysis using flow cytometry after staining with propidium iodide revealed that the treatment of M07E cells with FN did not block the entry of the cells into the cell cycle after stimulation with GM-CSF or SCF, whereas the treatment resulted in the appearance of subdiploid peak. Furthermore, FN was found to induce oligonucleosomal DNA fragmentation and chromatin condensation in the cells even in the presence of GM-CSF or SCF, suggesting the involvement of programmed cell death (apoptosis) in the FN-induced growth suppression. The growth suppression or apoptosis induced by FN was rescued by the addition of either anti-FN antibody, anti-very late antigen 5 monoclonal antibody (anti-VLA5 mAb), or GRGDSP peptide, but not by that of anti-VLA4 mAb or GRGESP peptide, suggesting that the FN effects on M07E cells were mediated through VLA5. In addition, the FN-induced apoptosis was detectable in VLA5-positive human hematopoietic cell lines other than M07E cells, but not in any of the VLA5-negative cell lines. These results suggest that FN is capable of inducing apoptosis via its interaction with VLA5, and also raise the possibility that the FN-VLA5 interaction may contribute, at least in part, to negative regulation of hematopoiesis.